On biomass milling for power generation - Williams, Orla (2016)
Biomass combustion has increasingly been used in pulverised fuel coal fired power stations as a way of addressing a wide range of emissions reduction targets. The reuse of existing equipment such as coal mills is essential to minimise the costs of conversion. However the fundamental fracture mechanics involved in biomass comminution are completely different to coal. Thus a thorough knowledge of the comminution properties of all biomass types in coal and biomass mills is necessary in order to minimise operational issues and to optimise milling and combustion.